An Analysis of Residential Mortgages and How Lending Standards and Regulations Have Changed Pursuant to the Financial Crisis of 2008. - Hampson, John D. (Tufts Archival Research Center, 2015)
This is an analysis of mortgages originated pre and post financial crisis to see how mortgage lending standards have changed since the crisis. This is in an attempt to better understand if the mortgage industry has become better regulated and more conscientious about their lending practices in an effort to avoid future crises.